MODEL OF COLLABORATIVE GOVERNANCE IN INDIGENOUS COMMUNITY BASED ECOTOURISM MANAGEMENT (A CASE STUDY IN NINO KONIS SANTANA NATIONAL PARK, TIMOR LESTE) - Ana Maria Do Rosario Carolina da Cruz Marito Magno Felicidade Xavier (FKIP UMN ALWASHLIYAH, 2026)
This research aims to analyze the implementation of a collaborative governance model in the management of indigenous community-based ecotourism within the Nino Konis Santana National Park (NKSNP), Timor-Leste. As a relatively new nation, Timor-Leste has designated tourism as a priority sector for economic development, with NKSNP serving as a primary destination due to its unique biodiversity and cultural richness. This study employs a descriptive qualitative method with a case study approach to gain an in-depth understanding of the dynamics of stakeholder interaction. Data was collected through in-depth interviews with key stakeholders, participant observation in community meetings, and a documentary study of relevant policies. The findings indicate that the collaboration process among the government, the Fataluku indigenous community, NGOs, and the private sector is ongoing but remains informal, reactive, and suboptimal. Several key challenges were identified, including significant imbalances in power and resources, the absence of a formal collaborative forum with legal legitimacy, limited community management capacity, and overlapping regulations between the tourism and conservation sectors. Despite these challenges, there is significant potential rooted in the local wisdom of Tara Bandu, which is upheld by the indigenous community as a philosophical and practical foundation for conservation. This study concludes that the collaborative governance model in NKSNP is still in its initial (formative) stage and requires a more inclusive institutional design, strong facilitative leadership, and a transparent benefit-sharing mechanism to transform into a sustainable and equitable ecotourism management system that benefits the local community.